Research Progress in Exosome-Based Nanoscale Drug Carriers in Tumor Therapies - Fu, Wei; Li, Tingting; Chen, Hongbo; Zhu, Shu; Zhou, Changkai (Frontiers in Oncology, 2022)
Current anti-tumor treatment methods have several reported limitations, including multi-drug resistance and serious adverse reactions. Targeted drug delivery systems are effective alternatives that can help healthcare providers overcome these limitations. Exosomes can serve as a natural nanoscale drug delivery system, with the advantages of high biocompatibility, low immunogenicity, and efficient tumor targetability. In this paper, we discuss the biological characteristics of exosomes, summarize the drug-carrying mechanisms of exosome-based drug delivery systems, and examine the potential role and applicability of exosomes in clinical tumor treatment approaches. Furthermore, we discuss the challenges of using exosomes as drug carriers, which provides a theoretical reference for future development of exosome-based delivery systems in clinical precision tumor treatment.